USA Hockey`s American development model: Changing the coaching and player development paradigm - Martel, K. (International Sport Coaching Journal, 2015)
Despite significant advances in the development and performance of United States-born hockey players since the 1970s, room for improvement remains, especially when one compares the U.S. to its top international competition, much of which succeeds at the Olympic and World Championship level with dramatically smaller pools of talent from which to assemble its elite teams. USA Hockey sought to address this performance discrepancy and fulfill the full potential of American hockey through creation and implementation of its American Development Model (ADM), a nationwide reinvention of how hockey was taught at the grassroots level. Based on long-term athlete development principles and founded on sport science and proven child development best practices, the ADM represents a revolution in athlete and coach development. This paper explores the research that helped create USA Hockey`s ADM, along with the initiative`s methodology, execution and early outcomes.